Visual Fixation Patterns During Viewing of Half-Face Stimuli in Adults: An Eye-Tracking Study - Galambos, Ágoston; Turcsán, Borbála; Oláh, Katalin; Elekes, Fruzsina; Gergely, Anna; Király, Ildikó; Topál, József (Frontiers in Psychology, 2018)
Human faces play a special role in social cognition, since as a core signal of interpersonal communication, they convey various kinds of information (e.g. about sex, age, race, emotions, intentions). Study 1 aimed to explore how this specialization manifests itself in eye movements when looking at neutral, static female faces. We monitored the gaze pattern of 23 adult participants using eye-tracking method. To test if model-driven processes are involved in face perception, and to see how inversion affects fixations on special facial stimuli, we presented vertically cut half-faces in upright and inverted positions (so half of each stimulus represented a half-face, whereas the other half was left blank). Our results corroborate prior findings consistently demonstrating the dominance of the triangular area marked by the eyes and the mouth, measured by number and duration of fixations. In addition, we found evidence for so-called complementary fixations, targeted at the non-informative parts (i.e. the half that does not contain any facial information) of the pictures, suggesting that other mechanisms beyond purely stimulus-driven ones might drive looking behavior when scanning faces. Study 2 was intended to test if these systematic eye movements are face-specific or occur in case of other visual objects as well.